Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae - Higuchi, Horácio; Birindelli, José L.o.; Sousa, Leandro M.; Britski, Heraldo A. (Zootaxa, 2007)
Merodoras nheco, new genus and species of Doradidae (Siluriformes) is described from Rio Paraguay basin, Brazil. The new genus belongs to the new subfamily Astrodoradinae, a monophyletic group formally named herein that includes, besides Merodoras, Amblydoras, Anadoras, Astrodoras, Hypodoras, Physopyxis, and Scorpiodoras. This group is diagnosed by the possession of: lacrimal serrated and participating in the orbital margin, four to seven pleural ribs; spines on the postcleithral process; postero-inferior portion of the coracoid exposed.  Merodoras nheco, new species, is distinguished from other doradids by the unique combination of the following characteristics: 1) tips of retrorse spines on the midlateral scutes ventrally oriented in adults; 2) incomplete lateral line, with only a few midlateral scutes anteriorly; 3) pectoral girdle entirely exposed ventrally, with the opening of the arrector ventralis inferior reduced to a small fossae on the anterior edge of the coracoid; 4) caudal fin truncate; 5) dorsal-fin spine smooth, without serrae on both faces; 5) lacrimal serrated; 6) lateral ethmoid serrated.  Merodoras nheco inhabits the “Pantanal Matogrossense,” a flooded portion of the upper Rio Paraguay basin in western Brazil.